2001
DOI: 10.1111/j.1553-2712.2001.tb02111.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Lidocaine for the Treatment of Migraine Headache: A Randomized, Controlled Trial

Abstract: Abstract. Objective: To evaluate the effect of intranasal lidocaine for immediate relief (5 minutes) of migraine headache pain. Methods: A randomized, double-blind, placebo-controlled clinical trial at two university-affiliated community teaching hospitals enrolled patients 18-50 years old with migraine headache as defined by the International Headache Society. Patients who were pregnant, lactating, known to abuse alcohol or drugs, or allergic to one of the study drugs, those who used analgesics within two hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 25 publications
0
41
1
1
Order By: Relevance
“…Historically, there have been anecdotal reports of SPG blockade as a successful modality to treat migraine and cluster headache, although not all studies have demonstrated success . Recently, Tepper et al demonstrated efficacy of an implanted electrical stimulator in the SPG in a group of subjects with intractable CM .…”
Section: Spg Blockadementioning
confidence: 81%
“…Historically, there have been anecdotal reports of SPG blockade as a successful modality to treat migraine and cluster headache, although not all studies have demonstrated success . Recently, Tepper et al demonstrated efficacy of an implanted electrical stimulator in the SPG in a group of subjects with intractable CM .…”
Section: Spg Blockadementioning
confidence: 81%
“…There have been a number of studies published over the years on SPG blockade, using intranasal lidocaine for the treatment of migraine, including one case report, an uncontrolled study, and four small, randomized trials . In 1999, Maizels published a case report of a 15‐year‐old boy who had episodic migraine with aura.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Side effects, which were transient and not serious, included bitter taste, nostril burning, and oropharyngeal numbness. Another randomized controlled study found that 1 mL of 4% intranasal lidocaine was not better than placebo in the acute treatment of migraine for patients presenting to the emergency department (ED) …”
Section: Pathophysiologymentioning
confidence: 99%
“…Results of randomized, double-blind studies indicate a modest, but significant efficacy although with frequent and early recurrence [102, 103]. …”
Section: Other Drugsmentioning
confidence: 99%